Parkinsonism associated with prolonged unresponsive wakefulness syndrome after blunt head injury: a clinico-pathological study - Kurt A. Jellinger (Free Neuropathology)
Objective: Survival after traumatic brain injury (TBI) and posttraumatic parkinsonian-like symptoms is increasing, in particular in those patients developing during disease course an unresponsive wakefulness syndrome (UWS) previously termed persistent vegetative state.